Thermal dye sublimation transfer paper coating and preparation method thereof
By forming a composite coating structure of a hydrophobic layer, an ink absorbing layer and a surface layer on the thermal sublimation transfer paper, the problem of poor adhesion and poor compatibility between the thermal sublimation transfer paper and the coating in the prior art is solved. , achieving higher ink absorption, faster transfer time and better image accuracy.
Patent Information
- Application Number
- CN202411572140.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The adhesion between the existing thermal sublimation transfer paper and the coating is not strong and compatibility is poor, resulting in a small amount of ink absorption and dye molecules penetration into the substrate paper affecting the dye transfer rate.
Using a thermal sublimation transfer paper coating composed of a hydrophobic layer, an ink absorbing layer and a surface layer, the hydrophobic layer is formed of a photothermal double cured polyurethane emulsion, and the ink absorbing layer is cross-linked by thiolated silica and acrylamide monomer, and the surface is The layer is composed of a polyvinyl alcohol solution.
The bonding force between the coating and the substrate paper and the adhesion and compatibility between the coating are improved, the ink absorption is increased, the transfer time is shortened, and the transfer efficiency and image accuracy are improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of transfer paper coatings, in particular to a thermal sublimation transfer paper coating and a preparation method thereof. Background Art
[0002] Thermal sublimation transfer is a new process that uses an inkjet printer equipped with thermal sublimation transfer ink to print portraits, landscapes, texts and other images on thermal sublimation transfer inkjet paper in a mirror image manner, and then heats it to about 200℃ through thermal transfer equipment to make the thermal transfer ink on the thermal sublimation paper sublimate and penetrate into the substrate, thereby realistically transferring the color image on the paper to textiles, porcelain cups, porcelain plates, porcelain boards, metals and other materials.
[0003] As the main functional material for carrying sublimation ink, the performance of thermal sublimation transfer paper coating directly affects the transfer effect. Thermal sublimation transfer paper coating usually uses sodium carboxymethyl cellulose, polyvinyl alcohol, etc. as adhesives, and porous inorganic materials such as silica, talc, and calcium carbonate as pigments. However, there are problems such as weak adhesion and poor compatibility between the existing thermal sublimation transfer paper and the coating. In addition, the currently used thermal sublimation transfer technology also has shortcomings such as low ink absorption and dye molecules penetrating into the substrate paper affecting the dye transfer rate, so it needs to be modified. Summary of the invention
[0004] The object of the present invention is to provide a thermal sublimation transfer paper coating and a preparation method thereof to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a thermal sublimation transfer paper coating and a preparation method thereof, wherein the thermal sublimation transfer paper coating comprises a hydrophobic layer coated on a substrate paper, an ink absorbing layer coated on the hydrophobic layer and a surface layer coated on the ink absorbing layer; on the substrate paper, the weight of the hydrophobic layer per square meter is 1-2.5 g, the weight of the ink absorbing layer per square meter is 5-8 g, and the weight of the surface layer per square meter is 2-4 g; the preparation method of the thermal sublimation transfer paper coating comprises the following steps: Step 1: By weight, 100 parts of photothermal dual-curing polyurethane emulsion, 0.3-0.5 parts of photoinitiator, and 10-14 parts of triethylenetetramine are mixed, coated on the substrate paper, and cured at 70-80° C. to form a hydrophobic layer; Step 2: Applying ink-absorbing layer coating onto the hydrophobic layer for UV curing, and drying the formed ink-absorbing layer; Step 3: The polyvinyl alcohol powder is dissolved in deionized water to obtain a polyvinyl alcohol solution; the polyvinyl alcohol solution is coated on the ink-absorbing layer and dried to form a surface layer.
[0006] Furthermore, in step 1, the preparation method of the photothermal dual-curing polyurethane emulsion is: mixing epoxy-terminated silicon-containing polyurethane and double-bond-terminated polyurethane in a mass ratio of (8-10):1, adding triethylamine to neutralize the pH to 7-7.5, and adding water to emulsify to obtain a photothermal dual-curing polyurethane emulsion with a solid content of 30-40%.
[0007] Furthermore, the preparation method of the epoxy-terminated silicon-containing polyurethane is as follows: vacuum dehydrating terminal hydroxyl polydimethylsiloxane and polyethylene glycol 1000 at 100-120°C for 1-2h, mixing the terminal hydroxyl polydimethylsiloxane and polyethylene glycol 1000 at a weight ratio of 1:(6-10) to obtain a mixed diol; adding 2-2.2 parts of isophorone diisocyanate to 3-3.5 parts of the mixed diol under nitrogen protection, using dibutyltin dilaurate as a catalyst, reacting at 70-80°C for 2-3h to obtain a silicon-containing prepolymer; cooling to 40-50°C, adding 0.27-0.36 parts of 1,4-butanediol for chain extension reaction for 0.5-1h; adding 1.2-1.3 parts of propylene glycol diglycidyl ester for end-capping reaction for 1-2h to obtain an epoxy-terminated silicon-containing polyurethane.
[0008] Furthermore, the preparation method of the double-bond terminated polyurethane comprises the following steps: S1: Weigh glycerol and epichlorohydrin, use concentrated sulfuric acid as a catalyst (the amount of concentrated sulfuric acid is 0.5-0.6% of the total weight of the reactants), heat to 50-60°C in a water bath and react for 3-4 hours, add 30-40% sodium hydroxide solution by mass concentration after cooling, react at 30-40°C for 3-4 hours, remove insoluble matter by suction filtration, remove water by reduced pressure distillation, and obtain glycerol monoglycidyl ether; S2: Treat polyethylene glycol 1000 with vacuum dehydration at 100-120°C for 1-2h, mix 11-15 parts of isophorone diisocyanate, 10 parts of polyethylene glycol 1000 and 2-3 parts of propylene glycol monoglycidyl ether by weight in a nitrogen environment, use dibutyltin dilaurate as a catalyst, react at 70-80°C for 1-3h, cool to 50-60°C, add 3-4.5 parts of 2-hydroxyethyl acrylate and react for 4-5h to obtain a double-bond terminated polyurethane.
[0009] Furthermore, in S1, the molar ratio of propylene glycol, epichlorohydrin and sodium hydroxide is 1:1:1.
[0010] Furthermore, the preparation method of the ink-absorbing layer coating is as follows: by weight, 30 to 50 parts of sodium carboxymethyl cellulose and 50 to 70 parts of acrylamide monomer are dissolved in 200 parts of deionized water, 0.3 to 0.5 parts of N, N-methylenebisacrylamide, 1 to 1.2 parts of glutaraldehyde, and 0.5 to 0.7 parts of a photoinitiator are added, and 4 to 5 parts of mercapto silica are added under stirring to obtain the ink-absorbing layer coating.
[0011] Furthermore, the preparation method of mercaptosilicic acid silica is as follows: by weight, 5 parts of anhydrous ethanol, 1 part of deionized water, 0.03-0.06 parts of ammonia water, and 0.02-0.05 parts of 3-mercaptopropyltrimethoxysilane are mixed, and stirred at 50-60° C. for 1-2 hours to obtain a mixed solution; 2-3 parts of nano-silica are added to 100 parts of the mixed solution, and the mixture is ultrasonically dispersed for 1-2 hours and then filtered, rinsed with anhydrous ethanol and deionized water, and dried to obtain mercaptosilicic acid silica.
[0012] Furthermore, in step 2, during UV curing, the exposure energy is 800-1000 mJ / cm 2 , the curing time is 60~90s.
[0013] Compared with the prior art, the beneficial effects achieved by the present invention are: The present invention provides a method for preparing a thermal sublimation transfer paper coating, wherein the coating is composited by a hydrophobic layer, an ink-absorbing layer, and a surface layer. The hydrophobic layer is formed by coating a photothermal dual-curing polyurethane emulsion on a substrate paper and curing it. In preparing the photothermal dual-curing polyurethane emulsion, the present invention first introduces terminal hydroxyl polydimethylsiloxane into a polyurethane prepolymer, and uses propylene glycol diglycidyl ester to block the end to obtain an epoxy-terminated silicon-containing polyurethane with good hydrophobic properties; then, glycerol monoglycidyl ether is synthesized using glycerol, epichlorohydrin, and sodium hydroxide as raw materials, and glycerol monoglycidyl ether is introduced into the polyurethane prepolymer as a chain extender, and hydroxyethyl acrylate is used to block the end to obtain a double-bond-terminated polyurethane; epoxy-terminated silicon-containing polyurethane and double-bond-terminated polyurethane are mixed to obtain a photothermal dual-curing polyurethane emulsion. The photothermal dual-curing polyurethane emulsion is coated on the substrate paper. Under the action of the curing agent, the epoxy groups in the two different polyurethanes are cross-linked to form a dense hydrophobic layer. The presence of the hydrophobic layer effectively prevents the dye molecules from entering the substrate paper, avoiding the substrate paper from being immersed in the dye.
[0014] The ink-absorbing layer coating is applied on the hydrophobic layer. During the curing process of the ink-absorbing layer, mercapto-silica, acrylamide monomer, and sodium carboxymethyl cellulose are cross-linked. Since the hydrophobic layer contains unsaturated carbon-carbon double bonds, the hydrophobic layer and the ink-absorbing layer are chemically bonded, which not only improves the adhesion but also improves the compatibility between the coatings. The interpenetrating network resin formed after the ink-absorbing layer is cured will expand when it absorbs water, thereby increasing the amount of ink absorbed; and silica has a porous structure, which can provide pores for the network resin, further increasing the amount of ink absorbed, shortening the transfer time, and improving the transfer efficiency.
[0015] The polyvinyl alcohol solution is coated on the ink-absorbing layer to form a surface layer. At room temperature, polyvinyl alcohol has a strong water permeability, while at high temperature, the hydrogen bonding effect between polyvinyl alcohol molecules is reduced, thereby providing larger gaps, which is conducive to the rapid and full sublimation of dye molecules from the coating material and improves the transfer effect.
[0016] The thermal sublimation transfer paper coating designed by the present invention not only has a strong bonding force with the substrate paper, but also has high adhesion and compatibility between the coatings, a good transfer effect, reduces ink penetration, burrs and image ghosting problems, and effectively improves the accuracy of the image. DETAILED DESCRIPTION
[0017] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0018] Materials and sources used in the present invention: The substrate paper is transfer printing base paper, and the paper density is 94g / m 3 , from Suzhou Zhihuibao Digital Technology Co., Ltd.; polyvinyl alcohol powder from Anhui Wanwei Group Co., Ltd., model 04-88 (L); terminal hydroxyl polydimethylsiloxane from Jiangsu Kexing New Materials Co., Ltd., model F-1.5; photoinitiator 184 from Shanghai Aladdin Biochemical Technology Co., Ltd.; nano-silica from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd., model XFI03; sodium carboxymethyl cellulose (molecular mass 4000, degree of substitution 1.2) from Jiangsu Paxter Co., Ltd.
[0019] Embodiment 1: A thermal sublimation transfer paper coating and a preparation method thereof, comprising the following steps: Step 1: 100g of light-heat dual-curing polyurethane emulsion, 0.5g of photoinitiator, and 14g of triethylenetetramine were mixed and coated on the substrate paper and cured at 70°C to form a 2.5g / m 2 The hydrophobic layer; wherein the preparation method of the photothermal dual-curing polyurethane emulsion comprises the following steps: S11: The terminal hydroxyl polydimethylsiloxane and polyethylene glycol 1000 were subjected to vacuum dehydration treatment at 120°C for 1 hour, and the terminal hydroxyl polydimethylsiloxane and polyethylene glycol 1000 were mixed at a weight ratio of 1:9 to obtain a mixed diol; 2.2 kg of isophorone diisocyanate was added to 3.5 kg of the mixed diol under nitrogen protection, and dibutyltin dilaurate was used as a catalyst to react at 70°C for 2 hours to obtain a silicon-containing prepolymer; the temperature was lowered to 40°C, 0.36 kg of 1,4-butanediol was added to extend the chain for 0.5 hours; 1.3 kg of propylene glycol diglycidyl was added for end-capping reaction for 1 hour to obtain an epoxy-terminated silicon-containing polyurethane; S12: Weigh glycerol and epichlorohydrin, use concentrated sulfuric acid as a catalyst (the amount of concentrated sulfuric acid is 0.5% of the total weight of the reactants), heat to 50°C in a water bath and react for 3 hours, add a 40% sodium hydroxide solution by mass after cooling, react at 30°C for 3 hours, remove insoluble matter by suction filtration, remove water by reduced pressure distillation, and obtain glycerol monoglycidyl ether; wherein the molar ratio of glycerol, epichlorohydrin, and sodium hydroxide is 1:1:1; S13: vacuum dehydrating polyethylene glycol 1000 at 120° C. for 1 h, mixing 13 kg of isophorone diisocyanate, 10 kg of polyethylene glycol 1000, and 2.5 kg of propylene glycol monoglycidyl ether by weight under a nitrogen environment, using dibutyltin dilaurate as a catalyst, reacting at 70° C. for 1 h, cooling to 50° C., adding 4.2 kg of 2-hydroxyethyl acrylate and reacting for 4 h to obtain a double-bond terminated polyurethane; S14: epoxy-terminated silicon-containing polyurethane and double-bond-terminated polyurethane are mixed in a mass ratio of 8:1, triethylamine is added to neutralize the pH to 7, and water is added to emulsify to obtain a photothermal dual-curing polyurethane emulsion with a solid content of 40%; Step 2: The ink-absorbing layer coating is applied to the hydrophobic layer for UV curing, with an exposure energy of 1000mJ / cm 2 The curing time is 60s and the dry form is 8g / m 2 The ink-absorbing layer; wherein the preparation method of the ink-absorbing layer coating comprises the following steps: S21: 5 kg of anhydrous ethanol, 1 kg of deionized water, 60 g of ammonia water, and 50 g of 3-mercaptopropyltrimethoxysilane were mixed, and stirred at 50° C. for 1 h to obtain a mixed solution; 3 g of nano-silicon dioxide was added to 100 g of the mixed solution, and the mixture was ultrasonically dispersed for 1 h, and then filtered, rinsed with anhydrous ethanol and deionized water, and dried to obtain mercaptosilicon dioxide; S22: 300 g of sodium carboxymethyl cellulose and 500 g of acrylamide monomer were dissolved in 2 kg of deionized water, 4 g of N,N-methylenebisacrylamide, 10 g of glutaraldehyde, and 5 g of photoinitiator were added, and 40 g of mercapto-silica was added under stirring to obtain an ink-absorbing layer coating; Step 3: The polyvinyl alcohol powder was dissolved in deionized water to obtain a polyvinyl alcohol solution with a mass concentration of 20%. The polyvinyl alcohol solution was applied to the ink-absorbing layer and dried to form a 4 g / m 2 Surface layer.
[0020] Embodiment 2: A thermal sublimation transfer paper coating and a preparation method thereof, comprising the following steps: Step 1: 100g of light-heat dual-curing polyurethane emulsion, 0.5g of photoinitiator, and 14g of triethylenetetramine were mixed and coated on the substrate paper and cured at 75°C to form a 2.5g / m 2 The hydrophobic layer; wherein the preparation method of the photothermal dual-curing polyurethane emulsion comprises the following steps: S11: The terminal hydroxyl polydimethylsiloxane and polyethylene glycol 1000 were subjected to vacuum dehydration treatment at 120°C for 1 hour, and the terminal hydroxyl polydimethylsiloxane and polyethylene glycol 1000 were mixed at a weight ratio of 1:9 to obtain a mixed diol; 2.2 kg of isophorone diisocyanate was added to 3.5 kg of the mixed diol under nitrogen protection, and dibutyltin dilaurate was used as a catalyst to react at 75°C for 2.5 hours to obtain a silicon-containing prepolymer; the temperature was lowered to 45°C, 0.36 kg of 1,4-butanediol was added to extend the chain for 0.5 hours; 1.3 kg of propylene glycol diglycidyl was added to cap the reaction for 1.5 hours to obtain an epoxy-capped silicon-containing polyurethane; S12: Weigh glycerol and epichlorohydrin, use concentrated sulfuric acid as a catalyst (the amount of concentrated sulfuric acid is 0.5% of the total weight of the reactants), heat to 55°C in a water bath and react for 3.5 hours, add a 40% sodium hydroxide solution by mass after cooling, react at 35°C for 3.5 hours, remove insoluble matter by suction filtration, remove water by reduced pressure distillation, and obtain glycerol monoglycidyl ether; wherein the molar ratio of glycerol, epichlorohydrin, and sodium hydroxide is 1:1:1; S13: vacuum dehydrating polyethylene glycol 1000 at 120° C. for 1 h, mixing 13 kg of isophorone diisocyanate, 10 kg of polyethylene glycol 1000, and 2.5 kg of propylene glycol monoglycidyl ether by weight under a nitrogen environment, using dibutyltin dilaurate as a catalyst, reacting at 75° C. for 2 h, cooling to 55° C., adding 4.2 kg of 2-hydroxyethyl acrylate and reacting for 4.5 h to obtain a double-bond terminated polyurethane; S14: epoxy-terminated silicon-containing polyurethane and double-bond-terminated polyurethane are mixed in a mass ratio of 8:1, triethylamine is added to neutralize the pH to 7, and water is added to emulsify to obtain a photothermal dual-curing polyurethane emulsion with a solid content of 40%; Step 2: The ink-absorbing layer coating is applied to the hydrophobic layer for UV curing, and the exposure energy is 900mJ / cm 2 The curing time is 75s and the dry form is 8g / m 2 The ink-absorbing layer; wherein the preparation method of the ink-absorbing layer coating comprises the following steps: S21: 5 kg of anhydrous ethanol, 1 kg of deionized water, 60 g of ammonia water, and 50 g of 3-mercaptopropyltrimethoxysilane were mixed, and stirred at 55° C. for 1.5 h to obtain a mixed solution; 3 g of nano-silicon dioxide was added to 100 g of the mixed solution, and the mixture was ultrasonically dispersed for 1.5 h, and then filtered, rinsed with anhydrous ethanol and deionized water, and dried to obtain mercapto-silicon dioxide; S22: 300 g of sodium carboxymethyl cellulose and 500 g of acrylamide monomer were dissolved in 2 kg of deionized water, 4 g of N,N-methylenebisacrylamide, 10 g of glutaraldehyde, and 5 g of photoinitiator were added, and 45 g of mercapto-silica was added under stirring to obtain an ink-absorbing layer coating; Step 3: Dissolve the polyvinyl alcohol powder in deionized water to obtain a polyvinyl alcohol solution with a mass concentration of 20%; apply the polyvinyl alcohol solution to the ink-absorbing layer and dry it to form a 4g / m 2 Surface layer.
[0021] Embodiment 3: A thermal sublimation transfer paper coating and a preparation method thereof, comprising the following steps: Step 1: 100g of light-heat dual-curing polyurethane emulsion, 0.5g of photoinitiator, and 14g of triethylenetetramine were mixed and coated on the substrate paper and cured at 80°C to form a 2.5g / m 2 The hydrophobic layer; wherein the preparation method of the photothermal dual-curing polyurethane emulsion comprises the following steps: S11: The terminal hydroxyl polydimethylsiloxane and polyethylene glycol 1000 were subjected to vacuum dehydration treatment at 120°C for 1 hour, and the terminal hydroxyl polydimethylsiloxane and polyethylene glycol 1000 were mixed at a weight ratio of 1:9 to obtain a mixed diol; 2.2 kg of isophorone diisocyanate was added to 3.5 kg of the mixed diol under nitrogen protection, and dibutyltin dilaurate was used as a catalyst to react at 80°C for 3 hours to obtain a silicon-containing prepolymer; the temperature was lowered to 50°C, 0.36 kg of 1,4-butanediol was added to extend the chain for 1 hour; 1.3 kg of propylene glycol diglycidyl was added for end-capping reaction for 2 hours to obtain an epoxy-terminated silicon-containing polyurethane; S12: Weigh glycerol and epichlorohydrin, use concentrated sulfuric acid as a catalyst (the amount of concentrated sulfuric acid is 0.5% of the total weight of the reactants), heat to 60°C in a water bath and react for 4 hours, add 40% sodium hydroxide solution by mass after cooling, react at 40°C for 4 hours, remove insoluble matter by suction filtration, remove water by reduced pressure distillation, and obtain glycerol monoglycidyl ether; wherein the molar ratio of glycerol, epichlorohydrin, and sodium hydroxide is 1:1:1; S13: vacuum dehydrating polyethylene glycol 1000 at 120° C. for 1 h, mixing 13 kg of isophorone diisocyanate, 10 kg of polyethylene glycol 1000, and 2.5 kg of propylene glycol monoglycidyl ether by weight under a nitrogen environment, using dibutyltin dilaurate as a catalyst, reacting at 80° C. for 3 h, cooling to 60° C., adding 4.2 kg of 2-hydroxyethyl acrylate and reacting for 5 h to obtain a double-bond terminated polyurethane; S14: epoxy-terminated silicon-containing polyurethane and double-bond-terminated polyurethane are mixed in a mass ratio of 8:1, triethylamine is added to neutralize the pH to 7, and water is added to emulsify to obtain a photothermal dual-curing polyurethane emulsion with a solid content of 40%; Step 2: Apply the ink-absorbing layer coating to the hydrophobic layer and cure it under UV light with an exposure energy of 1000 mJ / cm 2 The curing time is 90s and the dry form is 8g / m 2 The ink-absorbing layer; wherein the preparation method of the ink-absorbing layer coating comprises the following steps: S21: 5 kg of anhydrous ethanol, 1 kg of deionized water, 60 g of ammonia water, and 50 g of 3-mercaptopropyltrimethoxysilane were mixed, and stirred at 60° C. for 2 h to obtain a mixed solution; 3 g of nano-silicon dioxide was added to 100 g of the mixed solution, and the mixture was ultrasonically dispersed for 2 h, and then filtered, rinsed with anhydrous ethanol and deionized water, and dried to obtain mercapto-silicon dioxide; S22: 300 g of sodium carboxymethyl cellulose and 500 g of acrylamide monomer were dissolved in 2 kg of deionized water, 4 g of N,N-methylenebisacrylamide, 10 g of glutaraldehyde, and 5 g of photoinitiator were added, and 50 g of mercapto-silica was added under stirring to obtain an ink-absorbing layer coating; Step 3: Dissolve the polyvinyl alcohol powder in deionized water to obtain a polyvinyl alcohol solution with a mass concentration of 20%; apply the polyvinyl alcohol solution to the ink-absorbing layer and dry it to form a 4g / m 2 Surface layer.
[0022] Comparative Example 1: The coating was prepared using conventional techniques.
[0023] Mix 40g of nano-silicon dioxide, 300g of sodium carboxymethyl cellulose, 400g of polyvinyl alcohol and 2kg of deionized water, apply to the surface of the substrate paper, and dry to form a 14.5g / m 2 coating.
[0024] Comparative Example 2: No hydrophobic layer is provided, and other parameters are the same as those of Example 2.
[0025] Step 1: The ink-absorbing layer coating is applied to the substrate paper for UV curing, and the exposure energy is 900mJ / cm 2 The curing time is 75s and the dry form is 8g / m 2The ink-absorbing layer; wherein the preparation method of the ink-absorbing layer coating comprises the following steps: S1: 5 kg of anhydrous ethanol, 1 kg of deionized water, 60 g of ammonia water, and 50 g of 3-mercaptopropyltrimethoxysilane were mixed and stirred at 55° C. for 1.5 h to obtain a mixed solution; 3 g of nano-silicon dioxide was added to 100 g of the mixed solution, and the mixture was ultrasonically dispersed for 1.5 h and then filtered, rinsed with anhydrous ethanol and deionized water, and dried to obtain mercapto-silicon dioxide; S2: 300 g of sodium carboxymethyl cellulose and 500 g of acrylamide monomer were dissolved in 2 kg of deionized water, 4 g of N,N-methylenebisacrylamide, 10 g of glutaraldehyde, and 5 g of photoinitiator were added, and 45 g of mercapto-silica was added under stirring to obtain an ink-absorbing layer coating; Step 2: Dissolve polyvinyl alcohol powder in deionized water to obtain a polyvinyl alcohol solution with a mass concentration of 20%; apply the polyvinyl alcohol solution to the ink-absorbing layer and dry it to form a 4g / m 2 Surface layer.
[0026] Comparative Example 3: Epoxy-terminated silicon-containing polyurethane emulsion was used instead of the photothermal dual-curing polyurethane emulsion, and the other parameters were the same as those in Example 3.
[0027] Step 1: 100g epoxy-terminated silicone-containing polyurethane emulsion, 0.5g photoinitiator, and 14g triethylenetetramine were mixed and coated on the substrate paper and cured at 80°C to form a 2.5g / m 2 The hydrophobic layer; wherein the preparation method of the epoxy-terminated silicon-containing polyurethane emulsion comprises the following steps: S11: The terminal hydroxyl polydimethylsiloxane and polyethylene glycol 1000 were subjected to vacuum dehydration treatment at 120°C for 1 hour, and the terminal hydroxyl polydimethylsiloxane and polyethylene glycol 1000 were mixed at a weight ratio of 1:9 to obtain a mixed diol; 2.2 kg of isophorone diisocyanate was added to 3.5 kg of the mixed diol under nitrogen protection, and dibutyltin dilaurate was used as a catalyst to react at 80°C for 3 hours to obtain a silicon-containing prepolymer; the temperature was lowered to 50°C, 0.36 kg of 1,4-butanediol was added to extend the chain for 1 hour; 1.3 kg of propylene glycol diglycidyl was added for end-capping reaction for 2 hours to obtain an epoxy-terminated silicon-containing polyurethane; S12: adding triethylamine to the epoxy-terminated silicon-containing polyurethane to neutralize the pH to 7, and adding water to emulsify to obtain an epoxy-terminated silicon-containing polyurethane emulsion with a solid content of 40%; Step 2: Apply the ink-absorbing layer coating to the hydrophobic layer and cure it under UV light with an exposure energy of 1000 mJ / cm 2 The curing time is 90s and the dry form is 8g / m 2 The ink-absorbing layer; wherein the preparation method of the ink-absorbing layer coating comprises the following steps: S21: 5 kg of anhydrous ethanol, 1 kg of deionized water, 60 g of ammonia water, and 50 g of 3-mercaptopropyltrimethoxysilane were mixed, and stirred at 60° C. for 2 h to obtain a mixed solution; 3 g of nano-silicon dioxide was added to 100 g of the mixed solution, and the mixture was ultrasonically dispersed for 2 h, and then filtered, rinsed with anhydrous ethanol and deionized water, and dried to obtain mercapto-silicon dioxide; S22: 300 g of sodium carboxymethyl cellulose and 500 g of acrylamide monomer were dissolved in 2 kg of deionized water, 4 g of N,N-methylenebisacrylamide, 10 g of glutaraldehyde, and 5 g of photoinitiator were added, and 50 g of mercapto-silica was added under stirring to obtain an ink-absorbing layer coating; Step 3: Dissolve the polyvinyl alcohol powder in deionized water to obtain a polyvinyl alcohol solution with a mass concentration of 20%; apply the polyvinyl alcohol solution to the ink-absorbing layer and dry it to form a 4g / m 2 Surface layer.
[0028] Experiment: The performance of the thermal sublimation transfer papers prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested.
[0029] Coating adhesion: Refer to GB / T9286-1998 varnish and paint cross-cut test.
[0030] Transfer rate: The test method of transfer rate is to use a four-color desktop inkjet printer to print the four-color (100% C, 100% M, 100% Y, 100% K) color block pattern on digital thermal sublimation transfer paper. After drying, use a flatbed transfer machine to transfer the color block to white 100% polyester cloth. The transfer temperature is set to 200℃ and the time is 30s. Referring to the measurement requirements of reflection density in the standard "GB / T 18722-2002 Application of reflection density measurement and colorimetry in printing process control of printing technology", the color density of the four-color blocks on the cloth after transfer is tested by X-Rite 528 model color densitometer, which is the transfer color density; the density of the four-color blocks remaining on the paper after transfer is tested, which is the residual color density. The transfer rate of the four color block patterns on the transfer paper is tested and the average value is taken.
[0031] Transfer rate = transfer color density / (transfer color density+residual color density)×100%.
[0032] Transfer effect: Observe the transfer image accuracy and whether ghosting problems occur.
[0033] The experimental results are shown in Table 1.
[0034] Table 1. Performance tests of thermal sublimation transfer paper
[0035] Conclusion: The data of Examples 1 to 3 show that the thermal sublimation transfer paper coating prepared by the present invention has good performance. The data of Example 1 and Comparative Example 1 show that compared with conventional coatings, the coating of the present invention has good adhesion performance, the transfer rate during thermal transfer reaches more than 90%, the pattern accuracy is high and there is no ghosting problem; the data of Example 2 and Comparative Example 2 show that the hydrophobic layer in the present invention can not only improve the adhesion performance between the substrate paper and the ink-absorbing layer, but also prevent the dye molecules from combining with the substrate paper, thereby improving the thermal sublimation effect of the dye molecules and the transfer efficiency; the data of Example 3 and Comparative Example 3 show that in the light-heat dual-curing polyurethane emulsion, the presence of double-bond terminated polyurethane can make the bonding force between the formed hydrophobic layer and the ink-absorbing layer stronger, improve the adhesion and compatibility between the coatings, and achieve better transfer effect.
[0036] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a thermal sublimation transfer paper coating, characterized in that: The following steps are involved: Step 1: By weight, 100 parts of light-heat dual-curing polyurethane emulsion, 0.3-0.5 parts of photoinitiator, and 10-14 parts of triethylenetetramine were mixed, coated on the substrate paper, and cured at 70-80°C to form a 1-2.5 g / m 2 Hydrophobic layer; Step 2: Apply the ink-absorbing layer coating onto the hydrophobic layer and cure it with UV light to form a 5~8g / m 2 Ink absorbing layer; Step 3: Dissolve polyvinyl alcohol powder in deionized water to obtain a polyvinyl alcohol solution; apply the polyvinyl alcohol solution to the ink-absorbing layer and dry it to form a 2-4 g / m 2 Surface layer.
2. The method for preparing a thermal sublimation transfer paper coating according to claim 1, characterized in that: In step 1, the preparation method of the photothermal dual-curing polyurethane emulsion is: epoxy-terminated silicon-containing polyurethane and double-bond-terminated polyurethane are mixed in a mass ratio of (8-10):1, triethylamine is added to neutralize the pH to 7-7.5, and water is added to emulsify to obtain a photothermal dual-curing polyurethane emulsion with a solid content of 30-40%.
3. The method for preparing a thermal sublimation transfer paper coating according to claim 2, characterized in that: The preparation method of epoxy-terminated silicon-containing polyurethane is as follows: vacuum dehydrating terminal hydroxyl polydimethylsiloxane and polyethylene glycol 1000 for 1-2 hours at 100-120°C, mixing terminal hydroxyl polydimethylsiloxane and polyethylene glycol 1000 at a weight ratio of 1:(6-10) to obtain a mixed diol; adding 2-2.2 parts of isophorone diisocyanate to 3-3.5 parts of the mixed diol under nitrogen protection, using dibutyltin dilaurate as a catalyst, reacting at 70-80°C for 2-3 hours to obtain a silicon-containing prepolymer; cooling to 40-50°C, adding 0.27-0.36 parts of 1,4-butanediol for chain extension reaction for 0.5-1 hour; adding 1.2-1.3 parts of propylene glycol diglycidyl for end-capping reaction for 1-2 hours to obtain an epoxy-terminated silicon-containing polyurethane.
4. The method for preparing a thermal sublimation transfer paper coating according to claim 2, characterized in that: The preparation method of double-bond terminated polyurethane comprises the following steps: S1: Weigh glycerol and epichlorohydrin, use concentrated sulfuric acid as a catalyst, heat to 50-60°C in a water bath and react for 3-4 hours, add 30-40% sodium hydroxide solution by mass concentration after cooling, react at 30-40°C for 3-4 hours, remove insoluble matter by suction filtration, remove water by reduced pressure distillation, and obtain glycerol monoglycidyl ether; S2: Treat polyethylene glycol 1000 with vacuum dehydration at 100-120°C for 1-2h, mix 11-15 parts of isophorone diisocyanate, 10 parts of polyethylene glycol 1000 and 2-3 parts of propylene glycol monoglycidyl ether by weight in a nitrogen environment, use dibutyltin dilaurate as a catalyst, react at 70-80°C for 1-3h, cool to 50-60°C, add 3-4.5 parts of 2-hydroxyethyl acrylate and react for 4-5h to obtain a double-bond terminated polyurethane.
5. The method for preparing a thermal sublimation transfer paper coating according to claim 4, characterized in that: In S1, the molar ratio of glycerol, epichlorohydrin and sodium hydroxide is 1:1:
1.
6. The method for preparing a thermal sublimation transfer paper coating according to claim 1, characterized in that: The preparation method of the ink-absorbing layer coating is as follows: by weight, 30-50 parts of sodium carboxymethyl cellulose and 50-70 parts of acrylamide monomer are dissolved in 200 parts of deionized water, 0.3-0.5 parts of N,N-methylenebisacrylamide, 1-1.2 parts of glutaraldehyde, 0.5-0.7 parts of photoinitiator are added, and 4-5 parts of mercapto silicon dioxide are added under stirring to obtain the ink-absorbing layer coating.
7. The method for preparing a thermal sublimation transfer paper coating according to claim 6, characterized in that: The preparation method of mercaptosilica is as follows: according to weight parts, 5 parts of anhydrous ethanol, 1 part of deionized water, 0.03-0.06 parts of ammonia water, and 0.02-0.05 parts of 3-mercaptopropyltrimethoxysilane are mixed, and stirred at 50-60°C for 1-2 hours to obtain a mixed solution; 2-3 parts of nano-silica are added to 100 parts of the mixed solution, and the mixture is ultrasonically dispersed for 1-2 hours and then filtered, rinsed with anhydrous ethanol and deionized water, and dried to obtain mercaptosilica.
8. The method for preparing a thermal sublimation transfer paper coating according to claim 1, characterized in that: In step 2, when UV curing, the exposure energy is 800~1000mJ / cm 2 , the curing time is 60~90s.
9. The method for preparing a thermal sublimation transfer paper coating according to claim 1, characterized in that: The mass concentration of the polyvinyl alcohol solution is 15%~20%.
10. The thermal sublimation transfer paper coating prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Composite membrane quick-drying type dye-sublimation transfer printing digital paper
CN103381721A
Thermal sublimation and transfer digital paper with high ink suction amount
CN103397576A
Polyurethane-based super-hydrophobic coating and preparation method thereof
CN111117472A
Preparation method of short fluoroalkyl compound modified hydrophobic / super-hydrophobic waterborne polyurethane coating
CN115058183A
Photo-thermal conversion super-hydrophobic wind power blade surface protective coating and preparation method thereof
CN116970336A
Cited By
High-strength coating, preparation method and application in SMC (Sheet Molding Compound)
CN121022243A